PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS KEARIFAN LOKAL PADA MATERI ZAT ADITIF - Adriana Martania; Hairida Hairida; Rini Muharini; Eny Enawaty; Rahmat Rasmawan (Jurnal Education and Development, 2023)
The purpose of this study was to measure the validity and response of teachers to the developed Local Wisdom-Based Student Worksheets. The form of this research is development (R&D) with reference to the ADDIE development model which consists of analysis, design and development. The subject of this study was Student Worksheets Based on Local Wisdom which was piloted on three junior high school science teachers. The data collection instruments used were material validity questionnaires, language and graphics as well as teacher response questionnaires with data collection techniques in the form of indirect communication. Data analysis uses product validity criteria. The results of the data analysis showed that the Student Worksheets Based on Local Wisdom on Material Additives obtained valid criteria with an average material validity of 98.6%, language validity of 97.9% and material validity of 98.6% and based on the results of the teacher's response questionnaire to the Local Wisdom-Based Student Worksheet on Additive Materials received a good response with a percentage result of 90%. Therefore, the validity assessment and teacher response tests show that the Local Wisdom-Based Student Worksheet on Additive Material is valid for use by teachers and students in the learning process.